Prevalence of Small Intestinal Bacterial Overgrowth among Chronic Pancreatitis Patients: A Case-Control Study - Amelie Therrien; Simon Bouchard; Sacha Sidani; Mickael Bouin (Canadian Journal of Gastroenterology and Hepatology)
Background. Patients with chronic pancreatitis (CP) exhibit numerous risk factors for the development of small intestinal bacterial overgrowth (SIBO). Objective. To determine the prevalence of SIBO in patients with CP. Methods. Prospective, single-centre case-control study conducted between January and September 2013. Inclusion criteria were age 18 to 75 years and clinical and radiological diagnosis of CP. Exclusion criteria included history of gastric, pancreatic, or intestinal surgery or significant clinical gastroparesis. SIBO was detected using a standard lactulose breath test (LBT). A healthy control group also underwent LBT. Results. Thirty-one patients and 40 controls were included. The patient group was significantly older (53.8 versus 38.7 years; P < 0.01). The proportion of positive LBTs was significantly higher in CP patients (38.7 versus 2.5%: P < 0.01). A trend toward a higher proportion of positive LBTs in women compared with men was observed (66.6 versus 27.3%; P = 0.056). The subgroups with positive and negative LBTs were comparable in demographic and clinical characteristics, use of opiates, pancreatic enzymes replacement therapy (PERT), and severity of symptoms. Conclusion. The prevalence of SIBO detected using LBT was high among patients with CP. There was no association between clinical features and the risk for SIBO.